Use of psychotropic medications in relation to neuropsychiatric symptoms, cognition and functional performance in Alzheimer's disease over a three-year period: Kuopio ALSOVA study. (19th June 2017) - Törmälehto, Soili; Martikainen, Janne; Bell, J. Simon; Hallikainen, Ilona; Koivisto, Anne M.
ABSTRACT: Background: Psychotropic medications are widely prescribed to manage neuropsychiatric symptoms (NPS) of Alzheimer's disease (AD). Our objective was to investigate the longitudinal associations between psychotropic medication use and NPS, cognition, and functional performance in persons with very mild or mild AD at baseline. Methods: Data were collected as part of the prospective three-year study of home-dwelling persons with AD and their caregivers ( n = 236 dyads). The associations between psychotropic medication use and clinical measures were analyzed using repeated measures Generalized Estimating Equation (GEE) models. NPS, cognition, daily functioning, and disease severity were assessed with NPI, CERAD-NB, or MMSE, ADCS-ADL, and CDR-SOB, respectively. All analyses were adjusted for age, gender, education, and co-morbidities. Results: The prevalence of benzodiazepines and related medications increased from 16% to 24% ( p = 0.031), antidepressants from 11% to 18% ( p = 0.057), and antipsychotics from 4% to 16% ( p = 0.011) in the three years following AD diagnosis. In adjusted multivariable analyses, a one-point increase in NPI increased the odds of using any psychotropic medication class by 4% (odds ratio (OR) 1.04, 95% confidence interval (CI) 1.01–1.07). ADCS-ADL (1/OR 1.04, 95% CI 1.02–1.06) and CDR-SOB (OR 1.27, 95% CI 1.13–1.42) were associated with use of antipsychotics. CERAD-NB and MMSE were not associated with any psychotropic medication class use in the models. Conclusions: Psychotropic medication use increased significantly in relation to increasing dependency in AD, especially with NPS. Furthermore, the use of antipsychotics increased with disease severity, and with decline in daily functioning. Cognitive performance was not associated with psychotropic medication use.